Problems and Solutions: Utilization of Digital Media in Physical Education Subjects - Rahman, Andriyana Nur; Silvy Juditya; Bernhardin, Dindin; Zakaria, Dhani Agusni (STKIP Paasundan Press, 2024)
This study aims to describe the problems of teachers (physical education) in using digital media, solutions, and factors causing the emergence of problems for physical education teachers in the use of digital media. This research uses a qualitative approach with its type, namely exploratory descriptive. Data collection techniques in this study were carried out by observation and interviews. The subject of this study consists of 4 teachers, namely class X to XI teachers. Data analysis in this study used reduction, presentation, verification, and interpretation of findings. Based on data analysis, it can be concluded that there are problems for physical education teachers in the use of digital media in the era of the Merdeka curriculum such as limited access to wifi networks in terms of policies related to the use of digital media in schools , The solution that is usually done by physical education teachers is group learning with peers, collaborating with learning communities or with technology experts, while the factors causing the problem of lack of knowledge and understanding of physical education teachers are related to the use of digital media, abnormal electricity, personal devices that do not support, errors in an application, limiting certain links, unstable network connectivity